PENINGKATAN PERTUMBUHAN DAN HASIL KARET MELALUI SISTEM TUMPANG SARI BERBASIS KARET (Improvement The Growth and Yield of Rubber Through Rubber Based Intercropping System) - Sahuri Sahuri (Jurnal Penelitian Hutan Tanaman, 2020)
ABSTRACTThe rubber intercropping system with other economic crops can increase land productivity  and rubber productivity. This study aimed to research the effects of intercropping treatments towards soil fertility, development of rubber girth expansion, latex yield, and potential intercrops yields. The study was conducted at the experimental plantation of Sembawa Rubber Research Center using a Randomized Block Design with three replications. The treatment factors are four cropping patterns, i.e: PT1 (monoculture rubber); PT2 (rubber pineapple); PT3 (rubber+sweet corn); and PT4 (rubber+cayenne pepper). Observed parameters in this study included rubber girth expansion, bark thickness, amount of tappable trees, amount of latex yield, and amount of potential intercrops yields. The data were statistically analyzed using ANOVA, followed by DMRT at the level of 5%. The results showed that intercropping treatment significantly affects the growth of rubber trees and reduces unproductive plant phases. Rubber trees in the intercropping treatment were ready for tapping five months earlier than in the monoculture rubber trees. However, the bark thickness was similar to that of the monoculture rubber trees. Intercropping treatments had no effect on latex yield per tree per tapping, but yield per hectare was greater in the intercropping treatments than monocultur rubber trees due to the number of trees that could be tapped was significantly higher.                                                              ABSTRAKTumpang sari karet dengan tanaman ekonomis lainnya dapat meningkatkan produktivitas  lahan dan produktivitas karet. Penelitian ini bertujuan untuk mengetahui pengaruh perlakuan tumpang sari terhadap kesuburan tanah, pertumbuhan lilit batang karet/keliling batang karet, hasil lateks, dan potensi hasil tanaman sela. Penelitian dilaksanakan di Kebun Percobaan Pusat Penelitian Karet Sembawa menggunakan Rancangan Acak Kelompok dengan tiga ulangan. Faktor perlakuan ada empat pola tanam, yaitu PT1 (karet monokultur); PT2 (karet+nanas); PT3 (karet+jagung manis); dan PT4 (karet+cabai rawit). Parameter yang diamati meliputi: lilit batang karet, tebal kulit batang, matang sadap pohon karet, hasil lateks, potensi hasil tanaman sela dan analisis kesuburan tanah. Hasil penelitian menunjukkan bahwa perlakuan tumpang sari berpengaruh nyata terhadap peningkatan pertumbuhan pohon karet dan mengurangi fase tanaman yang tidak produktif. Pohon karet dengan perlakuan tumpang sari siap untuk disadap lima bulan lebih awal daripada pohon karet monokultur. Sementara ketebalan kulit batang karet tidak berbeda nyata daripada pohon karet monokultur. Perlakuan tumpang sari tidak memberikan pengaruh terhadap  hasil lateks per pohon per penyadapan, tetapi hasil per hektar lebih besar dengan perlakuan tumpang sari karena jumlah pohon yang dapat disadap lebih tinggi secara nyata.